2021
DOI: 10.37349/ei.2021.00010
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between mesenchymal stromal cells and immune system: clinical applications in immune-related diseases

Abstract: Mesenchymal stromal cells (MSCs) are a mesodermal stem cell population, with known self-renewal and multilineage differentiation properties. In the last century, MSCs have been widely used in regenerative medicine and tissue engineering approaches. MSCs initially were isolated from bone marrow aspirates, but currently have been identified in a great number of tissues of the human body. Besides their utilization in regenerative medicine, MSCs possess significant immunoregulatory/immunosuppressive properties, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 157 publications
0
33
0
Order By: Relevance
“…Initially, the characterization of the thawed WJ and BM-MSCs was performed, and no discrepancies were observed according to the already published literature[ 22 - 24 ]. Both thawed WJ and BM-MSCs fulfilled the criteria outlined by the ISCT and hence were considered as well-defined cells[ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initially, the characterization of the thawed WJ and BM-MSCs was performed, and no discrepancies were observed according to the already published literature[ 22 - 24 ]. Both thawed WJ and BM-MSCs fulfilled the criteria outlined by the ISCT and hence were considered as well-defined cells[ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…WJ-MSCs possess more naïve cells compared to MSCs derived from adult sources. Moreover, it has been shown that MSCs derived from fetal tissues are characterized by fewer mutations and epigenetic modifications, greater proliferation, and differentiation capacity, compared to adult MSCs[ 22 ] In addition, MSCs from fetal tissues can be isolated noninvasively (compared to adult MSCs)[ 22 ]. Allogeneic MSCs are considered immune-evasive cells, as they are not expressing either the HLA-DR or stimulatory (CD40) and co-stimulatory molecules (CD80 and CD86)[ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WJ was also used in this study for its important content of MSC, immune evasive cells showing an important potential for tissue engineering applications with interesting immunomodulation properties ( Weiss et al, 2008 ; El Omar et al, 2014 ; Li and Hua, 2017 ; Mallis et al, 2021 ). WJ-MSC were mechanically collected by applying the explant method based on the ability of cells to migrate out of the tissue and adhere to the culture surface.…”
Section: Methodsmentioning
confidence: 99%